Аналіз актуальних проблемних питань щодо перспективної асиметричної криптографії - Горбенко, Юрій Іванович; Акользіна, Ольга Сергіївна; Подгайко, Владислав Олегович (Kamianets-Podilskyi National Ivan Ohiienko University, 2018)
An analysis of current research on cryptography on lattices is given. The analysis takes place in accordance with the most relevant algorithms that have gone through the second stage of the US NIST competition. Some of them are combined — include several similar algorithms from the past stage. For a detailed consideration of them, a number of relevant topics for post-quantum algorithms are presented, which allows them to be described and categorized more substantially